2009
DOI: 10.1093/jnci/djp167
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Estrogen Receptor–Positive and –Negative Breast Cancer and Single–Nucleotide Polymorphism 2q35-rs13387042

Abstract: The rs13387042 is associated with both ER-positive and ER-negative breast cancer in European women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
2
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 7 publications
6
63
2
2
Order By: Relevance
“…However, the selection factors are unlikely to be related to the SNPs of interest. Furthermore, established susceptibility loci have shown the expected associations/odds ratios (ORs) in the GC-HBOC study population [Ahmed et al, 2009;Dunning et al, 2009;Frank et al, 2005;Milne et al, 2009;Shephard et al, 2009].…”
Section: Study Populationmentioning
confidence: 99%
“…However, the selection factors are unlikely to be related to the SNPs of interest. Furthermore, established susceptibility loci have shown the expected associations/odds ratios (ORs) in the GC-HBOC study population [Ahmed et al, 2009;Dunning et al, 2009;Frank et al, 2005;Milne et al, 2009;Shephard et al, 2009].…”
Section: Study Populationmentioning
confidence: 99%
“…Several genome wide association studies (GWAS) have identified the 2q35 region as associated with breast cancer risk (2)(3)(4)(5). Recent work has revealed the complexity of chromatin interactions in the 2q35 region (6) and its involvement in transcriptional regulation of neighbouring gene, IGFBP5 (MIM: 146734).…”
Section: Introductionmentioning
confidence: 99%
“…Stacey et al identifi ed a SNP on 2q35, a region with no known genes, as associated with breast cancer in Icelandic patients with ER + breast cancer [ 36 ]. Milne et al also found an association with ER − disease, although there was a stronger signal for ER+ [ 41 ]. Other breast cancer associations include signals on 3p24, potentially relating to the genes SLC4A7 or NEK10, and on 17q22, perhaps related to COX11.…”
Section: Common Low-penetrance Breast Cancer Genesmentioning
confidence: 99%